Partners with Bad Temper: Reject or Cure? A Study of Chronic Pain and Aggression in Horses - Fureix, Carole; Menguy, Hervé; Hausberger, Martine (PLOS ONE, 2010)
Background Experiencing acute pain can affect the social behaviour of both humans and animals and can increase the risk that they exhibit aggressive or violent behaviour. However, studies have focused mainly on the impact of acute rather than chronic painful experiences. As recent results suggest that chronic pain or chronic discomfort could increase aggressiveness in humans and other mammals, we tested here the hypothesis that, in horses, aggression towards humans (a common source of accidents for professionals) could be linked to regularly reported vertebral problems of riding horses. Methodology/Principal Findings Vertebral examination and standardized behavioural tests were made independently on the same horses. Here we showed that most horses severely affected by vertebral problems were prone to react aggressively towards humans (33/43 horses, chi-square test, df = 1, χ2 = 12.30, p<0.001), which was not the case for unaffected or slightly affected horses (9/16 horses, chi-square test, df = 1, χ2 = 0.25, p>0.05). The more affected they were, the fewer positive reactions they exhibited (rs = −0.31, p = 0.02). Conclusions/Significance This is to our knowledge the first experimental evidence of such a link between chronic discomfort/potential pain (inferred from the presence of vertebral problems) and aggression, suggesting that chronic painful experiences may act in ways similar to those of acute experiences. Chronic discomfort or pain may often be overlooked when facing “bad tempered” individuals, whether humans or animals. This experimental study confirms the importance of including chronic discomfort or pain as a major factor in interpersonal relations and models of aggression.